Fibre typing of intrafusal fibres. Issue 2 (August 2015) - Thornell, Lars‐Eric; Carlsson, Lena; Eriksson, Per‐Olof; Liu, Jing‐Xia; Österlund, Catharina; Stål, Per; Pedrosa‐Domellöf, Fatima
Abstract The first descriptions of muscle spindles with intrafusal fibres containing striated myofibrils and nervous elements were given approximately 150 years ago. It took, however, another 100 years to establish the presence of two types of intrafusal muscle fibres: nuclear bag and nuclear chain fibres. The present paper highlights primarily the contribution of Robert Banks in fibre typing of intrafusal fibres: the confirmation of the principle of two types of nuclear bag fibres in mammalian spindles and the variation in occurrence of a dense M‐band along the fibres. Furthermore, this paper summarizes how studies from the Umeå University group (Laboratory of Muscle Biology in the Department of Integrative Medical Biology) on fibre typing and the structure and composition of M‐bands have contributed to the current understanding of muscle spindle complexity in adult humans as well as to muscle spindle development and effects of ageing. The variable molecular composition of the intrafusal sarcomeres with respect to myosin heavy chains and M‐band proteins gives new perspectives on the role of the intrafusal myofibrils as stretch‐activated sensors influencing tension/stiffness and signalling to nuclei.